Power pyramid, hidden debt, and China’s urban expansion - Zhang, Juanfeng; Li, Lele; Zhang, Danxia; Han, Rui; Zhou, Jiangxing; Zhang, Lihua (International Journal of Strategic Property Management, 2022)
Chinese urban spatial expansion leads to inefficient use of land resources. This study uses the data of 289 cities from 2007 to 2018 and uses panel data models to test the driving mechanism of urban expansion. The study derives three conclusions. First, there is a significant positive correlation between urban power hierarchy and urban spatial expansion. If the urban administrative power hierarchy is high, then the urban built-up area increases more. Second, there is a significant positive correlation between the scale of hidden debt and the expansion of urban space. The increase of the urban investment bonds’ scale will promote the expansion of urban built-up areas. Third, there is a significant positive correlation between the quantity of bond issuers and urban spatial expansion.First published online 04 January 2023